The Influence of The Monopoly-Assisted PAKEM Model on Students' Critical Thinking Skill in Elementary School - Muhamad Afandi; Yulina Ismiyanti; Sari Yustiana; Bela Fina Apriliya (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to examine the effect of the monopoly-assisted PAKEM model (Active, effective, creative, effective and fun learning model) on the critical thinking skills of grade 5 students of SD Negeri Demaan. Research using quantitative methods with experimental research types. The experimental design form used Quasi Experimental Design with the form of Nonequivalent Control Group Design. The study involved two groups: an experimental class and a control class. The subjects in this study were grade 5 Demaan state elementary school which amounted to 45 students. Data collection is in the form of a description type test of 10 questions given for pretest and posttest. The data analysis techniques used are normality, homogeneity and hypothesis test consisting of Independent sample t-test and Paired sample t test. Before carrying out the data collection process, conducting instrument trials first consists of validity, reliability, differentiation and difficulty tests. The average pretest result of the control class was 40.83 and the posttest was 40.95 While the average experimental class pretest results obtained were 44.06 and posttest obtained 80.63. The paired sample t test of the experimental class obtained results in the lower column of -41.90 upper of -31.23 and the significance value (2-tailed) = 0.000 < 0.05 then Ho was rejected and Ha was accepted that there was a significant effect of using the monopoly-assisted PAKEM model on the critical thinking ability of grade 5 students of Demaan state elementary school. Therefore, educators or teachers can apply the Monopoly-assisted PAKEM model to improve students' critical thinking.